Seeley's Essentials of Anatomy & Physiology - VanPutte, Cinnamon L. [et al.] (Dubuque McGraw-Hill, 2010)
Designed for the one-semester course, Seeley's Essentials of Anatomy and Physiology is written to allow instructors the ability to accomplish one overall goal: to teach the basics of A&P while fostering the skill of problem solving. Through learning how to solve problems and think critically, students learn A&P based on two themes: the relationship between structure and function, and homeostasis.
Includes Colored Illustrations and Index
Keywords: Human physiology